Global analysis of sustainable development in context of quality and security of human life - Zgurovsky, M.Z. (Навчально-науковий комплекс "Інститут прикладного системного аналізу" НТУУ "КПІ" МОН та НАН України, 2009)
A system of factors (indices and indicators) and a new method of quantitative and qualitative evaluation are developed. This system, named “Sustainable Development Gauging Matrix” (SDGM) and data presented by reliable international organizations culminated in a Global Simulation regarding quality of life and security of the world population. Specifically, this study focuses on analysis of the Systematic Regularity of World Conflicts over the Course of Time. A prognosis is detailed of the next world conflict, labeled the "Conflict of XXI Century”, and an analysis is provided of its nature and main characteristics; duration, main phases of the conflict and intensity. This prognosis details a set of basic global threats that spawn this conflict. Using cluster analysis, its influence on different countries of the world is accurately defined. These results were obtained by applying the capabilities of the world data centers network as a tool for providing a variety of scientific interdisciplinary data. Запропоновано систему факторів (індексів та індикаторів) і розроблено нову метрику для вимірювання процесів сталого розвитку (SDGM) з метою глобального моделювання зазначених процесів у контексті якості й безпеки життя населення світу. Для цього моделювання використано вихідні дані, представлені авторитетними міжнародними організаціями. Із застосуванням SDGM проведено дослідження впливу сукупності глобальних загроз і світових конфліктів на сталий розвиток. Зроблено спробу передбачення наступного конфлікту, названого «конфліктом XXI сторіччя», і виконано аналіз його природи й головних характеристик: тривалості, основних фаз плину та інтенсивності. Визначено систему глобальних загроз, які породжують цей конфлікт. З використанням методу кластерного аналізу визначено вплив цих загроз на різні країни світу. Предложена система факторов (индексов и индикаторов) и разработана новая метрика для измерения процессов устойчивого развития (SDGM) с целью глобального анализа указанных процессов в контексте качества и безопасности жизни населения мира. Для этого моделирования использованы данные, представленные авторитетными международными организациями. С применением SDGM исследовано влияние совокупности глобальных угроз и мировых конфликтов на устойчивое развитие. Сделана попытка предвидения следующего конфликта, названного «конфликтом XXI столетия», и выполнен анализ его природы и главных характеристик: продолжительности, основных фаз течения и интенсивности. Определена система глобальных угроз, порождающих этот конфликт. С использованием метода кластерного анализа определено влияние этих угроз на различные страны мира.